Optimal. Leaf size=32 \[ 5+e^{\frac {1}{x}-x} \left (3 \left (4+e^2\right )-\frac {e^{2-2 x}}{x^2}\right ) \]
________________________________________________________________________________________
Rubi [A] time = 0.18, antiderivative size = 46, normalized size of antiderivative = 1.44, number of steps used = 4, number of rules used = 3, integrand size = 74, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.041, Rules used = {14, 6706, 2288} \begin {gather*} 3 \left (4+e^2\right ) e^{\frac {1}{x}-x}-\frac {e^{-3 x+\frac {1}{x}+2} \left (3 x^2+1\right )}{\left (\frac {1}{x^2}+3\right ) x^4} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 14
Rule 2288
Rule 6706
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \left (-\frac {3 e^{\frac {1}{x}-x} \left (4+e^2\right ) \left (1+x^2\right )}{x^2}+\frac {e^{2+\frac {1}{x}-3 x} \left (1+2 x+3 x^2\right )}{x^4}\right ) \, dx\\ &=-\left (\left (3 \left (4+e^2\right )\right ) \int \frac {e^{\frac {1}{x}-x} \left (1+x^2\right )}{x^2} \, dx\right )+\int \frac {e^{2+\frac {1}{x}-3 x} \left (1+2 x+3 x^2\right )}{x^4} \, dx\\ &=3 e^{\frac {1}{x}-x} \left (4+e^2\right )-\frac {e^{2+\frac {1}{x}-3 x} \left (1+3 x^2\right )}{\left (3+\frac {1}{x^2}\right ) x^4}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.28, size = 32, normalized size = 1.00 \begin {gather*} 3 e^{\frac {1}{x}-x} \left (4+e^2\right )-\frac {e^{2+\frac {1}{x}-3 x}}{x^2} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.70, size = 48, normalized size = 1.50 \begin {gather*} \frac {3 \, {\left (x^{2} e^{2} + 4 \, x^{2}\right )} e^{\left (-\frac {x^{2} - 1}{x}\right )} - e^{\left (-\frac {3 \, x^{2} - 2 \, x - 1}{x}\right )}}{x^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [B] time = 0.15, size = 58, normalized size = 1.81 \begin {gather*} \frac {3 \, x^{2} e^{\left (-\frac {x^{2} - 2 \, x - 1}{x}\right )} + 12 \, x^{2} e^{\left (-\frac {x^{2} - 1}{x}\right )} - e^{\left (-\frac {3 \, x^{2} - 2 \, x - 1}{x}\right )}}{x^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.18, size = 38, normalized size = 1.19
method | result | size |
risch | \(\frac {\left (3 x^{2} {\mathrm e}^{2}+12 x^{2}-{\mathrm e}^{-2 x +2}\right ) {\mathrm e}^{-\frac {\left (x -1\right ) \left (x +1\right )}{x}}}{x^{2}}\) | \(38\) |
norman | \(\frac {\left (3 \,{\mathrm e}^{2}+12\right ) x^{3} {\mathrm e}^{\frac {-x^{2}+1}{x}}-x \,{\mathrm e}^{-2 x +2} {\mathrm e}^{\frac {-x^{2}+1}{x}}}{x^{3}}\) | \(51\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.43, size = 30, normalized size = 0.94 \begin {gather*} \frac {{\left (3 \, x^{2} {\left (e^{2} + 4\right )} e^{\left (2 \, x\right )} - e^{2}\right )} e^{\left (-3 \, x + \frac {1}{x}\right )}}{x^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 5.92, size = 37, normalized size = 1.16 \begin {gather*} \frac {{\mathrm {e}}^{\frac {1}{x}-3\,x}\,\left (12\,x^2\,{\mathrm {e}}^{2\,x}-{\mathrm {e}}^2+3\,x^2\,{\mathrm {e}}^{2\,x+2}\right )}{x^2} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.43, size = 32, normalized size = 1.00 \begin {gather*} \left (12 + 3 e^{2}\right ) e^{\frac {1 - x^{2}}{x}} - \frac {e^{\frac {1 - x^{2}}{x}} e^{2 - 2 x}}{x^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________